Crepidotus eucalyptinus and Simocybe haustellaris: two uncommon species found in Central Spain (MYCOTAXON, 2008)
Crepidotus eucalyptinus and Simocybe haustellaris were collected together from a Quercus ilex subsp. ballota forest in Central Spain (Guadalajara Province). Collections of both species are described and their taxonomically distinctive microscopic characters are illustrated. The superficial similarity between these two brown-spored taxa is discussed as well as the taxonomic status of the former within Crepidotus and the close affinity of the species with Naucoria decolorata from Morocco and Spain.

Crepidotus eucalyptinus and Simocybe haustellaris: two uncommon species found in Central Spain - Bandala, Victor M.; Montoya, Leticia; Esteve-Raventos, Fernando (MYCOTAXON, 2008)
Crepidotus eucalyptinus and Simocybe haustellaris were collectedtogether from a Quercus ilex subsp. ballota forest in Central Spain (Guadalajara Province). Collections of both species are described and their taxonomically distinctive microscopic characters are illustrated. The superficial similarity between these two brown-spored taxa is discussed as well as the taxonomic status of the former within Crepidotus and the close affinity of the species with Naucoria decolorata from Morocco and Spain.
The following values have no corresponding Zotero field: pub-location: PO BOX 264, ITHACA, NY 14851-0264 USA publisher: MYCOTAXON LTD
Keywords: Crepidotaceae; taxonomy; wood-inhabiting fungi